Do Job Resources Matter for The Sales Force? Enhancing Sales Force Performance and Adaptive Selling Behavior - Imanirrahma Salsabil; Ratih Hurriyati; Puspo Dewi Dirgantari; Lili Adi Wibowo (Universitas Muhammadiyah Yogyakarta, 2023)
This study was carried out to examine the influence of emotional regulation as an individual's personal resource on the sales force performance by considering the mediating role of adaptive selling behavior and the moderating role of perceived job autonomy. Using a quantitative approach, data were obtained from 135 sales forces in the banking services industry in DKI Jakarta and Bandung City, selected using a purposive sampling method. The data obtained were then processed using structural equation modeling with partial least squares. The findings of this study empirically confirm the conservation of resources theory in terms of sales force performance, as emotional regulation acts as the personal resource that can, directly and indirectly, affect sales force performance through adaptive selling behavior. In addition, perceived job autonomy acts as the external resource that can strengthen the influence of emotional regulation on adaptive selling behavior, as well as adaptive selling behavior on sales force performance. The findings of this study also emphasize the need for management, especially sales managers, to ensure that their salespeople have a customer orientation and are willing to dedicate the energy and resources they possess to meet customer requests or needs.